17th century holographs in a personal miscellany of D. Francisco Manuel de Melo - Pereira, Elsa (2022)
Not many documents qualify as material evidence of 17th century holographs in Portugal. However, personal miscellanies can provide valuable insight into textual composition and transmission in the literary scene of the time. One of the examples worth exploring is a miscellaneous volume of papers collected by D. Francisco Manuel de Melo (1608-1666), which includes several manuscripts either written by the owner himself or by the hand of fellow contemporary poets. These are clean copies with few or no layers of revision, but still relevant to a certain kind of genetic criticism without drafts (GRÉSILLON, 1993), focused on the interstices of scribal activity and distributed authorship in the early modern period. The article examines little-explored documentation from the national archive Torre do Tombo, thus broadening the scope of genetic studies into the realm of Portuguese baroque literature.